Sanguinarine Attenuates Lipopolysaccharide-induced Inflammation and Apoptosis by Inhibiting the TLR4/NF-κB Pathway in H9c2 Cardiomyocytes - Meng, Yan-yan; Liu, Yuan; Hu, Zhe-fu; Zhang, Yao; Ni, Jian; Ma, Zhen-guo; Liao, Hai-han; Wu, Qing-qing; Tang, Qi-zhu (Current medical science, 2018)
Summary The inflammatory response is involved in the pathogenesis of the most common types of heart disease. Sanguinarine (SAN) has various pharmacological properties such as anti-inflammatory, antioxidant, antibacterial, antitumor, and immune-enhancing properties. However, few studies have investigated the effects of SAN on lipopolysaccharide (LPS)-induced inflammatory and apoptotic responses in H9c2 cardiomyocytes. Therefore, in this study, H9c2 cells were co-treated with SAN and LPS, and the mRNA levels of pro-inflammation markers and the apoptosis rate were measured to clarify the effect of SAN on cardiac inflammation. The underlying mechanism was further investigated by detecting the activation of Toll-like receptor (TLR)4/nuclear factor-κB (NF-κB) signaling pathways. As a result, increased mRNA expression of interleukin (IL)-1β, IL-6, and TNFα induced by LPS was attenuated after SAN treatment; LPS-induced apoptosis of H9c2 cardiomyocytes and cleaved-caspase 8, 9, 3 were all significantly reduced by SAN. Further experiments showed that the beneficial effect of SAN on blocking the inflammation and apoptosis of H9c2 cardiomyocytes induced by LPS was associated with suppression of the TLR4/NF-κB signaling pathway. It was suggested that SAN suppressed the LPS-induced inflammation and apoptosis of H9c2 cardiomyocytes, which may be mediated by inhibition of the TLR4/NF-κB signaling pathway. Thus, SAN may be a feasible therapy to treat sepsis patients with cardiac dysfunction.